Metal occurrence and textural-compositional properties in bottom sediments from right margin tributaries of the lower del Plata basin (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Sediment metal geochemistry from different surface water basins of South America has recently started to be investigated, together with textural properties of transported materials. The objective of the present study is to analyze and compare the metal contents in bottom sediments from down-stream positions of eight drainage basins running across eolic and water-reworked substrate materials from the Pampean loess, in relation to matrix composition, stream location and geomorphology from a relevant area of the del Plata basin. The sector, under the influence of extensive crop agriculture, holds more than half of Argentine's population and the largest country industrial sittings. Sampling, included extraction of cores (25 cm average recovery) from both margins at a 50 cm water-depth, from equivalent distal positions of different fluvial basins of the Undulated Pampa discharging into the Paraná river (del Medio, Ramallo, Tala, Arrecifes, Areco), were analyzed and also compared with those discharging into the Río de la Plata estuary (Carnaval-Martín, del Gato and del Pescado). A comparison with selected upstream positions was also included. Standardized methods for the determination of granulometric parameters, clay mineral composition, and metal contents were employed. Assessment of differences between rivers and metal content was done by ANOVA-MANOVA. Dot plot diagrams were used to observe distribution and trends of metal contents and matrix components. Almost 50% of samples fall in the mud and sandy mud sediment classification, and the majority of the rest in sandy silt field. Distal sediments from the northern sector show lower clay and organic matter contents than the southern sector rivers. Illite is the main clay component in all streams. Smectite and kaolinite levels are also high in streams flowing to the Río de la Plata. Metal contents indicate that Fe and Mn concentrations are very variable. The order of abundance for all studied metals, considering raw mean contents, is Fe>Mn>Pb>Cu> Cr>Ni>Cd, with lower mean values in the northern sector streams. Comparisons between clay, organic matter, and raw metal contents show significant correlations with most metals only for the northern streams. Statistical analysis with ANOVA-MANOVA between streams, metal contents, and stream locations indicate significant differences between all streams (p < 0.0000) for all metals (raw and grain size normalized data for clay and also silt plus clay). The comparison of streams from the northern sector shows no significant differences (p < 0.000) between them, with both raw and normalized metal contents. Cluster analysis shows the presence of two main clusters grouping both stream sectors. We can conclude that the northern sector streams are significantly similar and are in correspondence with a higher homogeneity of provenance materials along the courses. On the contrary, the southern streams are more variable, especially considering a different depositional environment in their distal positions. Also, a higher influence of antropic activities could be observed in this sector. Control of metal-polluted sites could be introduced taken into account existent experience in sediment management programs and local projects for the protection of the Rio de la Plata estuary under bilateral agreement between Argentina and Uruguay.
Keywords: Streambed sediments; Metal content; Textural properties; Clay minerals; Lower Paraná-Río de la Plata